MECHANICAL PROPERTIES OF CONCRETE CLOTH USING 3D FIBER MASH (CAHIERS MAGELLANES-NS, 2024)
This paper explores the development and mechanical properties of Concrete Cloth, a unique material formed using a three-dimensional fiber mesh. Concrete Cloth is a composite material that combines the structural strength of concrete with the flexibility and ease of deployment of fabric. The fiber mesh serves as a reinforcement network within the concrete matrix, enhancing its tensile strength and ductility. This study investigates the manufacturing process of Concrete Cloth, including the selection of fibers, weaving techniques, and impregnation methods. Mechanical testing is conducted to evaluate the material's performance under various loading conditions, including tensile, compressive, and flexural tests. The results demonstrate the effectiveness of the fiber 3D mesh in improving the mechanical properties of Concrete Cloth, including its resistance to cracking, deformation, and abrasion.